A MCC finite element approximation of incompressible miscible displacement in porous media. (September 2015) - Li, Xindong; Rui, Hongxing
Abstract In this paper, we analyze an efficient numerical scheme for the coupled system of incompressible miscible displacement in porous media. Mass-conservative characteristic finite element is used for concentration equation, which continuous velocities are needed. Therefore we solve flow equation by mixed finite element method with continuous flux approximation. Then we show this scheme preserves the mass balance identity and optimal <alternatives><inline-graphic xlink:href="ark:/27927/pgj2h017ptd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />l∞(L2)</alternatives> error estimate of the concentration. Numerical experiments are given to confirm the convergence and the property of mass balance.